2017
DOI: 10.3389/fpsyg.2017.00548
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Behavior Consistency among Older and Younger Adults When Looking at Emotional Faces

Abstract: The identification of non-verbal emotional signals, and especially of facial expressions, is essential for successful social communication among humans. Previous research has reported an age-related decline in facial emotion identification, and argued for socio-emotional or aging-brain model explanations. However, more perceptual differences in the gaze strategies that accompany facial emotional processing with advancing age have been under-explored yet. In this study, 22 young (22.2 years) and 22 older (70.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 94 publications
3
25
1
Order By: Relevance
“…For each of the facial expressions, older adults spent significantly less time on the eye region than younger adults, but we did not observe any age-related differences for the mouth region. These novel results are in contrast with previous studies (Chaby et al, 2017; Murphy & Isaacowitz, 2010; Wong et al, 2005) which showed that younger and older adults do not prioritise the same facial regions when identifying facial expressions (i.e., an exploratory strategy in young adults and a focusing strategy on the mouth region in older adults). What is new in this study is that participants focused primarily on the eye area during the decoding of facial expressions, although this was less evident in the older age group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For each of the facial expressions, older adults spent significantly less time on the eye region than younger adults, but we did not observe any age-related differences for the mouth region. These novel results are in contrast with previous studies (Chaby et al, 2017; Murphy & Isaacowitz, 2010; Wong et al, 2005) which showed that younger and older adults do not prioritise the same facial regions when identifying facial expressions (i.e., an exploratory strategy in young adults and a focusing strategy on the mouth region in older adults). What is new in this study is that participants focused primarily on the eye area during the decoding of facial expressions, although this was less evident in the older age group.…”
Section: Discussioncontrasting
confidence: 99%
“…Successful social interactions are crucial in everyday life and until old age. However, so far, studies in the field of psychology of aging have mainly investigated offline social interactions, with low ecological validity, in which participants are passive detached observers of social stimuli (e.g., Chaby et al, 2017; Grainger et al, 2017; Sze et al, 2012). Thus, it is not clear whether age-related differences remain in more natural interactive settings that offer the possibility to exchange social signals, especially through gaze behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this replay of eye movements is accompanied by image-specific patterns of brain activity during recall (Bone et al, 2019). Indeed, eye-tracking has been used to investigate strategies in many cognitive domains, such as learning (for a review, see Lai et al, 2013), reading (for a review, see Rayner, 1998), memory (for a review, see Hannula et al, 2010), face recognition (Chaby et al, 2017), and navigation (Mueller et al, 2008;Livingstone-Lee et al, 2011;Andersen et al, 2012). This link between eye movements and cognition extends to the solving of spatial tasks (Thomas and Lleras, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Madsen, Larson, Loschky, and Rebello ( 2012 ) used ScanMatch to examine differences in the eye movements of individuals answering physics questions to examine if there was a difference for correct versus incorrect answers. This method has also been used to examine differences in scanning patterns between Novices and Experts evaluating paintings (Pihko et al, 2011 ) and while viewing surgical procedures (Kübler, Eivazi, & Kasneci, 2015 ), problem-solving (Nyamsuren & Taatgen, 2013 ), face-processing (Chaby, Hupont, Avril, Luherne-du Boullay, & Chetouani, 2017 ), and decision-making (Zhou et al, 2016 ). Anderson, Anderson, Kingstone, and Bischof ( 2015 ) compared the ability of several scan path comparison methods to reveal similarities both within and between individuals looking at natural scenes and concluded that ScanMatch is a remarkable improvement on more simple method string-edit and linear distance methods.…”
Section: Introductionmentioning
confidence: 99%